Digital divide civic engagement, information poverty, and the Internet worldwide - Norris, Pippa (Cambridge Cambridge University Press, 2001)
There is widespread concern that the explosive growth of the Internet is exacerbating existing inequalities between the information rich and poor. Digital Divide sets out to examine the evidence for access and use of the Internet in 179 nations across the world. A global divide is evident between industrialized and developing societies. A social divide is apparent between rich and poor within each nation. And within the online community, evidence for a democratic divide is emerging between those who do and do not use Internet resources to engage, mobilize and participate in public life.
Includes bibliographical references (p. 273-285) and index.
Keywords: Digital divide